Evaluation of self efficacy and quality of life of stroke patients - OĞUZ, SIDIKA (My University, 2021)
Aim: Self-efficacy and quality of life affect each other positively. However, level of self-efficacy and quality of life and their relation to recovery of stroke patients are unclear. The study was designed as a methodological and randomized controlled experimental study to analyze self-efficacy and quality of life of stroke patients. Methods: The population of the study included stroke patients who received outpatient care at an acute stroke center between March – November, 2016. The study was performed with 72 patients. The patients in the experimental group received educational booklet and were included in a 3-month follow-up. The data for the study were collect using a Questionnaire Form, Quality of Life Scale for Stroke Patients, SSEQ and Monthly Follow-up Form. Standard tests, Tukey test, and regression and correlation analyses were used to analyze the data. Results: It was determined that the experimental group given the educational booklet and monthly follow-up had higher scores in both selfefficacy and quality of life than the patients in control group. In the experimental group, the analysis between total scores from SSEQ and SSQOL demonstrated increased correlation coefficient for the second visit compared with the first visit. Self-efficacy was positively correlated with the mobility, upper extremity function and self-care domains, and was negatively correlated with the language domain. Conclusion: As a result, it was determined that education and follow-up in stroke patients are effective and has positive impact on self-efficacy and quality of life

Amaç: Öz yeterlilik ve yaşam kalitesi birbirini olumlu yönde etkiler. Bununla birlikte, öz-etkililik ve yaşam kalitesi düzeyleri ve bunların inme hastalarının iyileşmesiyle ilişkisi belirsizdir. Çalışma, inme hastalarının öz-etkililiğini ve yaşam kalitesini analiz etmek için metodolojik ve randomize kontrollü deneysel bir çalışma olarak tasarlanmıştır. Yöntem: Araştırmanın evrenini, Mart-Kasım 2016 tarihleri arasında akut inme merkezinde ayakta tedavi gören inme hastaları oluşturdu. Çalışma deney ve kontrol toplam 72 hasta ile yapıldı. Deney grubundaki hastalara eğitim kitapçığı ve 3 aylık takip girişimi uygulandı. Çalışmanın verileri Anket Formu, İnmeli Hastalar İçin Yaşam Kalitesi Ölçeği, SSEQ ve Aylık Takip Formu kullanılarak toplandı. Verilerin analizinde standart testler, Tukey testi ve regresyon ve korelasyon analizleri kullanıldı. Bulgular: Eğitim kitapçığı ve aylık izlem uygulanan deney grubundaki hastalarda öz yeterlik ve yaşam kalitesi puanlarının daha yüksek olduğu belirlendi. Deney grubunda, SSEQ ve SS-QOL'den alınan toplam puanlar arasındaki korelasyona bakıldığında, ilk görüşmeye kıyasla ikinci görüşmede artış olduğu görüldü. Öz-yeterlik, hareketlilik, üst ekstremite işlevi ve öz bakım alanları ile pozitif, dil alanı ile negatif korelasyon gösterdi. Sonuç: Sonuç olarak inmeli hastalarda eğitim ve aylık takibin, özyeterlilik ve yaşam kalitesi üzerinde olumlu etkisi olduğu belirlendi.
İnmeli hastalarda öz etkililik ve yaşam kalitesinin değerlendirilmesi
Keywords: Hasta Eğitimi; Hemşire Müdahalesi; İnme; ÖzEtkililik; Yaşam Kalitesi; Nursing Intervention; Quality of Life; Patient Education; Self-Efficacy; Stroke